Identification of potential AMPK activator by pharmacophore modeling, molecular docking and QSAR study. (April 2019) - Li, Yingying; Peng, Jiale; Li, Penghua; Du, Haibo; Li, Yaping; Liu, Xingyong; Zhang, Li; Wang, Liang-Liang; Zuo, Zhili
Graphical abstract: Highlights: AMPK is a newly therapeutic target for metabolic diseases and we have built Pharmacophore as a fast tool for virtual screening. In this study, ADMET filtering，molecular docking, QSAR analysis are applied to discover novel potential candidates. The method of MD simulation is used to investigate the binding stability of AMPK with the potential candidates. This study may be a reference for the development of AMPK activators and a foundation for further research. Abstract: AMP-activated protein kinase (AMPK) plays a major role in maintaining cellular energy homeostasis by sensing and responding to AMP/ADP concentrations relative to ATP. AMPK has attracted widespread attention as a potential therapeutic target for metabolic diseases such as cancer and cardiovascular diseases. The structure-based 3D pharmacophore model was developed based on the training set. The best pharmacophore model Hypo5 was proposed and validated using a decoy set, an external test set. Hypo5, with the correlation coefficient value of 0.936, cost difference value of 112.08 and low RMS value of 1.63, includes a ionizable positive, a hydrogen bond donor, a hydrogen bond acceptor and two hydrophobic features, which showed a high goodness of fit and enrichment factor. Thus it was used as a 3D query to find potential activator from the SPECS Database. Then the ADMET descriptors were used to filter all of 158 screening molecules. The 41 filtering compounds were subsequently subjected to molecular docking and Quantitative structure–activity relationship (QSAR) analysis. Finally, the compound H2 was picked out from those filtering compounds based on the receptor-ligand interaction analysis and the prediction of the QSAR models. And then it was submitted for molecular dynamics (MD) simulations to explore the stability of complex. The result indicates that the candidate could be considered a potential AMPK activator.